Declining Responsiveness of Childhood Plasmodium Falciparum Infections to Artemisinin-Based Combination Treatments Ten Years Following Deployment as First-Line Antimalarials in Nigeria. - Folarin, Onikepe (Infectious Disease of Poverty, 2019)
Background: The development and spread of artemisinin-resistant Plasmodium falciparum malaria in Greater Mekong Subregion has created impetus for continuing global monitoring of efficacy of artemisinin-based combination therapies (ACTs). This post analyses is aimed to evaluate changes in early treatment response markers 10 years after the adoption of ACTs as first-line treatments of uncomplicated falciparum malaria in Nigeria. Methods: At 14 sentinel sites in six geographical areas of Nigeria, we evaluated treatment responses in 1341 children under 5 years and in additional 360 children under 16 years with uncomplicated malaria enrolled in randomized trials of artemether-lumefantrine versus artesunate-amodiaquine at 5-year interval in 2009–2010 and 2014–2015 and at 2-year interval in 2009–2010 and 2012–2015, respectively after deployment in 2005 Results: Asexual parasite positivity 1 day after treatment initiation (APPD1) rose from 54 to 62% and 2 days after treatment initiation from 5 to 26% in 2009–2010 to 2014–2015 (P = 0.002 and P < 0.0001, respectively). Parasite clearance time increased significantly from 1.6 days (95% confidence interval [CI]: 1.55–1.64) to 1.9 days (95% CI, 1.9–2.0) and geometric mean parasite reduction ratio 2 days after treatment initiation decreased significantly from 11 000 to 4700 within the same time period (P < 0.0001 for each). Enrolment parasitaemia > 75 000 μl − 1 , haematocrit > 27% 1 day post-treatment initiation, treatment with artemether-lumefantrine and enrolment in 2014–2015 independently predicted APPD1. In parallel, KaplanMeier estimated risk of recurrent infections by day 28 rose from 8 to 14% (P = 0.005) and from 9 to 15% (P = 0.02) with artemether-lumefantrine and artesunate-amodiaquine, respectively. Mean asexual parasitaemia half-life increased significantly from 1.1 h to 1.3 h within 2 years (P < 0.0001). Conclusions: These data indicate declining parasitological responses through time to the two ACTs may be due to emergence of parasites with reduced susceptibility or decrease in immunity to the infections in these children.